DEVELOPMEMT OF PILOT SCALE DEALUMINATION UNIT OF 2.5 kg METAKAOLIN PER BATCH CAPACITY (Nigerian Journal of Technology, 2017)
A pilot-size dealumination unit to handle 2.5kg of metakaolin per batch was designed and fabricated and test run. The metakaolin was prepared from Kankara kaolin. The metakaolin was completely split into silica and alumina. The silica component which was inert to the sulphuric acid used during the reaction and was obtained as a solid product. While the alumina which reacted with the sulphuric acid was obtained in liquid form as aluminum sulphate, known as alum. The dealumination unit comprises of the dealumination reactor, known as dealuminator, acid holding tank and metakaolin slurry mixing tank. The material of construction selected for the dealumination reactor was stainless steel type 304 lined internally with glass to withstand the corrosive environment of the concentrated sulphuric acid at the reaction temperature > 140°C. The capacity of the componentsare; acid holding tank 5 liters;metakaolin slurry mixing tank 20 liters, with 70 W capacity motor and the dealuminator 50 liters, which had pressure relief valve, pressure gauge (0-10 bars) and temperature gauge (0 - 300°C) on the cover. Woven glass fiber cloth was used as lagging material to minimize heat lossto the surrounding. The purity level of the silica obtained from the reaction was above 95%.The endothermic nature of the dealumination process was void of external heating. http://dx.doi.org/10.4314/njt.v36i3.24